LIBERALISASASI PERDAGANGAN DAN DAMPAKNYA TERHADAP KINERJA PERDAGANGAN PRODUK KAYU INDONESIA DI PASAR ASEAN - Elvida Yosefi Suryandari; Deden Djaenudin; Indartik Indartik; Iis Alviya (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2018)
Trade liberalization in ASEAN has an impact on the reduction of tariff and non-tariff trade barriers so that it encouraging economic integration. This integration is expected to improve the performance of timber trade (HS44) among ASEAN countries. The aim of this study was to determine the effect of trade liberalization in ASEAN market toward the trade performance of Indonesian timber products. The approach used consists of analysis ofmarket share and balance of trade. The results showed that in general, trade liberalization in ASEAN market has an effect on the performance of trade in Indonesian wood products, especially when the ASEAN Trade in Goods Agreement (ATIGA) scheme was implemented in 2010. At that time, wood and wooden furniture tariff were set at 0%.  Non-tariff barrier of HS44 consist of certificates of origin of timber as a pre-requirement of duty-free import, and timber legality certification. Within the scope of ASEAN, wood market share is dominated by Malaysia (as a market leader) and Thailand. While in the world wood product market, Indonesia has become the competitors of Malaysia. The enhancement of Indonesian’s wood competitiveness needs to be done by overcoming non-tariff barriers and trade policies that more take sides on the timber industries.